2008
DOI: 10.1158/1535-7163.mct-07-2261
|View full text |Cite
|
Sign up to set email alerts
|

Differential antiproliferative mechanisms of novel derivative of benzimidazo[1,2-α]quinoline in colon cancer cells depending on their p53 status

Abstract: In the present article, we describe a mechanistic study of a novel derivative of N-amidino-substituted benzimidazo [1,2-A]quinoline in two human colorectal cancer cell lines differing in p53 gene status. We used a proteomic approach based on two-dimensional gel electrophoresis coupled with mass spectrometry to complement the results obtained by common molecular biology methods for analyzing cell proliferation, cell cycle, and apoptosis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…In addition, GTNs exhibited significantly lower expression levels of maspin and higher expression levels of m-p53 than rHMs. The results of the present study also indicated that the expression of maspin was inversely correlated with the expression of m-p53 in HMs, which was similar to the results reported for gastric cancer (29,30). Furthermore, the expression of maspin was inversely correlated, and that of m-p53 positively correlated, with a number of prognostic factors, including serum β-hCG levels, uterine size and diameter of theca-lutein cysts; however, age was not found to be associated.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, GTNs exhibited significantly lower expression levels of maspin and higher expression levels of m-p53 than rHMs. The results of the present study also indicated that the expression of maspin was inversely correlated with the expression of m-p53 in HMs, which was similar to the results reported for gastric cancer (29,30). Furthermore, the expression of maspin was inversely correlated, and that of m-p53 positively correlated, with a number of prognostic factors, including serum β-hCG levels, uterine size and diameter of theca-lutein cysts; however, age was not found to be associated.…”
Section: Discussionsupporting
confidence: 91%
“…99,[111][112][113] Several processes were originally associated with and were then shown to be dispensable for (at least some instances of) mitotic catastrophe. These include, but are not limited to, the activation of the DNA damage-responsive protease caspase-2, 114 of the tumor suppressor TP53 109,115 and of other members of the TP53 family, including the TP73 variant TAp73. 116,117 In view of recent results from several laboratories indicating that mitotic aberrations can induce cell senescence, [118][119][120] and that cell death can be either apoptotic or necrotic, 8 we have recently proposed a novel definition and categorization of mitotic catastrophe based on purely functional considerations.…”
Section: Definition Of 'Mitotic Catastrophe'mentioning
confidence: 99%
“…Even though a similar concentration-dependent antiproliferative pattern and caspase 7 activation (Figure 1B) were observed for both compounds, the cell cycle dynamics (Table 1) and percentage of apoptotic cell distribution (Table S1 in Supplementary Information) were somewhat different. The possibility of tested derivatives acting differently in the same cell line was thus studied in detail by global proteomic profiling, which proved successful in elucidating the molecular mechanisms triggered by novel antitumor compounds [17]. …”
Section: Resultsmentioning
confidence: 99%